Log transformations: What not to expect when you're expecting. Issue 5 (4th March 2022) - Bridges, William C.; Calkin, Neil J.; Kenyon, Catherine M.; Saltzman, Matthew J.
Abstract: We note that log transformations can be problematic when the variance of the underlying distribution is other than very small. We illustrate these problems in terms of lognormal sampling issues, interval estimation of the mean, and comparison of lognormal and logbinomial distributions with similar means and variances.